Dedna eliptocitoza - Zupan, Anja (Medicinski razgledi, 2006)
Hereditary elliptocytosis is a clinically, biochemically and genetically heterogeneous group of inherited disorders of red blood cells. It is characterised by the presence of elongated, oval or elliptically shaped erythrocytes on the peripheral blood smear. The elliptocytic phenotype has been shown to result from various defects of proteins that constitute membraneskeletal network. This network and molecules that bind it to the lipidbilayer are responsible for the shape of red blood cell and the stabilityand deformability of its membrane. This article will concentrate on findings about molecular anatomy of erythrocyte membrane and membrane skeleton, mutations of genes for structural proteins of elliptocytic membrane skeleton and functional changes of these proteins and interactions among them,their influences on mechanical properties of the membrane and consequentially on the cellular shape.
Keywords: kri; eritrociti; celična membrana; molecular biology; molekularna biologija; disease; bolezni; dedne bolezni; dedna eliptocitoza